ANALYSIS OF THE EFFECT OF PRODUCT QUALITY, PRICE AND HALAL LABELING ON PURCHASING DECISIONS (Case Studies Abon Sapi Pada Suka 68 Boyolali) - Putri Salsabila, Fanny Aulia; Handayani, Rini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to collect data that could be used to provide a definitive explanation of the impact of elements such as product quality, price, and halal labeling on consumer purchasing choices. In this study, quantitative research design was used as research design. One way of data collection is through the use of questionnaires, which are then examined through the application of multiple regression. Based on research findings, there is a positive and significant influence on purchasing decisions that can be caused by three factors: (1) product quality, (2) price, and (3) halal labeling. There are a total of 85.4% of factors influencing the purchase of Abon Daging Sapi Pada Suka 68 Boyolali. These factors include product quality, product price, and halal label. While the remaining 14.6% was influenced by additional factors that were not studied in this study. Keywords: product quality, price, halal labeling, purchasing decision